2020
DOI: 10.1212/cpj.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

PSP-like syndrome after aortic surgery in adults (Mokri syndrome)

Abstract: BackgroundA rare progressive supranuclear palsy–like syndrome seemingly triggered by aortic surgery was first described in 2004. This largest case series to date describes the features of this syndrome.MethodsWe searched the Mayo Clinic electronic medical records using the advanced cohort explorer search engine for patients evaluated for neurologic symptoms after cardiac-aortic surgery in the past 30 years. Data were extracted to Microsoft Excel from the identified patients and included clinical and neuroimagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is a rare disorder appearing after ascending aorta surgery. The typical symptoms include supranuclear gaze palsy, gait imbalance and dysarthria ( Mokri et al, 2004 ; Tisel et al, 2020 ). AD differs from other tauopathies in the presence of β-amyloid peptide, but not only the neurodegenerative basis of this disease but also the correlation between AD and CVD attracts interest of the researchers in this field ( Liesz, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is a rare disorder appearing after ascending aorta surgery. The typical symptoms include supranuclear gaze palsy, gait imbalance and dysarthria ( Mokri et al, 2004 ; Tisel et al, 2020 ). AD differs from other tauopathies in the presence of β-amyloid peptide, but not only the neurodegenerative basis of this disease but also the correlation between AD and CVD attracts interest of the researchers in this field ( Liesz, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…43 Occurring after aortic surgery, this relatively uncommon syndrome is characterized by a triad of supranuclear gaze palsy, dysarthria and gaze disturbance (Table 3). [43][44][45][46][47][48][49][50][51][52][53][54][55][56] Although it is suggested that there is a higher prevalence of this syndrome in men, this is likely due to the higher prevalence of thoracic aortic aneurysms and abdominal aortic dissections in men.…”
Section: Aortic Surgerymentioning
confidence: 99%
“…43 One possible explanation postulated for Mokri syndrome is the use of profound hypothermia (12.5°C to 30°C) during aortic surgeries in comparison to other cardiac surgeries. 44 Although hypothermia is considered a neuroprotective strategy, patients may develop ischemia if rewarming is carried out rapidly. Furthermore, this ischemia may further impact patients who develop hyperglycemia during hypothermia.…”
Section: Aortic Surgerymentioning
confidence: 99%
See 2 more Smart Citations